Alternative design of front door side impact beam for Nissan Navara - Calonghi, Andrea (Cranfield University, 2006)
In this thesis the aim is to assess the performances of the circular side-impact beam of Nissan Navara / Pathfinder considered in isolation and subjected to a bending test. Established the performances of the actual design in term of Force – displacement, comparing also the results with a bending test on the isolated beam, the following step is to start with the initial design of new open section beams to identify which of the beams designed could substitute the actual circular one. For the new design the evaluation is not only based on the comparison with the Force – displacement graph obtained with test and simulations for the actual circular design, but also on the comparison between the weight of the new designs and of the current side impact beam. Even if the cost is an other parameter of choice, in this thesis it has not been really considered, because the study for the new design is only at the initial phase.